Eosinophilic esophagitis an update in children - Votto, Martina; Naso, Matteo; Clemente, Andrea Martina; De Filippo, Maria; Gargiulo, Ginevra; Granone, Veronica; Siri, Giulia; Marseglia, Gian Luigi; Licari, Amelia (Acta Biomedica Atenei Parmensis, 2022)
Eosinophilic esophagitis (EoE) is an emerging antigen-mediated, inflammatory disease of unknown etiology. EoE affects about 1/2,000 patients in the United States (US), with a higher prevalence rate in adults (43.4/100,000) than in children (29.5/100,000), prevailing in Caucasians and male sex. EoE is a multifactorial disease typically characterized by type 2 inflammation. Pathogenesis is not entirely understood and is likely non-IgE mediated. Food allergens trigger EoE, stimulating the dysregulated immune cells through an impaired esophageal epithelial barrier. Clinical presentation of EoE depends on age and mainly includes food refusal, vomiting, abdominal or chest pain, dysphagia, and food impaction. Endoscopy is the gold standard to diagnose EoE. The goal of EoE therapy is to achieve clinical and histological remission to prevent esophageal fibrosis and improve patients’ quality of life (QoL). Cornerstones of therapy are PPIs, topical steroids, and elimination diets. Over recent decades, research progress has been made in terms of a greater understanding of the EoE pathogenesis and new therapeutic approaches. However, there are still several unmet needs, such as non-invasive tools and biomarkers for monitoring the disease.